The Relationship Between Cognitive Abilities and the Decision-Making Process: The Moderating Role of Self-Relevance - Jin, Menghan; Ji, Lingling; Peng, Huamao (Frontiers in Psychology, 2019)
This study investigated the relationship between cognitive abilities and age differences in information search and the moderating role of task self-relevance by measuring the decision-making processes of participants in both high and low self-relevance decision-making tasks. The sample included 57 young and 65 older adults. They viewed five-alternative × five-attribute decision matrices that required them to open, with a mouse click, the information cells that interested them. Processing speed, verbal fluency, working memory, and vocabulary were measured as cognitive abilities. The dependent variables were search engagement (including time-related engagement and frequency-related engagement) and search pattern (calculated based on alternative-based or attribute-based search). The results from structured equation modeling showed that age negatively predicted these cognitive abilities (processing speed, verbal fluency, working memory, and vocabulary) and positively predicted information search engagement. Processing speed mediated the effect of age on study time per cell under tasks with both high and low self-relevance. Verbal fluency, meanwhile, mediated the total search time and checking time per cell when the task was highly self-related but not when the task had low self-relevance. These results suggest that self-relevance can moderate the mediation effect of verbal fluency on the relationship between age and information search time; this means that older adults whose verbal fluency was limited require relatively more time to search information to make an informed decision. However, this effect is only sufficient when the decision-making task is highly self-related and provokes more engagement motivation toward it.